2016
DOI: 10.21474/ijar01/995
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Migraine Among Female Students at Taibah University, Kingdom of Saudi Arabia.

Abstract: Background:-University studentsare routinelycomplaining of triggers, especiallyirregular sleepand stress, which are commonly associated with migraineattacks. Objectives:-To assess the prevalenceof migraine headache among female students at Taibah University (Saudi Arabia) and to determine the common triggering and palliative factors of migraine headache among female University students. Methods:-A cross-sectional study was carried out among female university students.Participants who had suffered from two or m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
12
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 23 publications
5
12
1
Order By: Relevance
“…Unexpectedly, there was significant association between migraine headache and studying in non-health colleges (P =0.001) [1,2]. This agreed with previous, where migraine prevalence was higher among theoretical collage in comparison to practical collage (26%) and (56%) respectively.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…Unexpectedly, there was significant association between migraine headache and studying in non-health colleges (P =0.001) [1,2]. This agreed with previous, where migraine prevalence was higher among theoretical collage in comparison to practical collage (26%) and (56%) respectively.…”
Section: Discussionsupporting
confidence: 83%
“…In this study, lack of sleep (89.3%) is the most common trigger factor for migraine, followed by stress 74.8%, and menstruation 46.6%; Neyaz etal who showed that life style changes as (change in sleep pattern) in (66.0%) and stress in (56.1%). Whereas in other studies (1,2,18) irregular sleep was reported in 80.6%, stress in 83.5% of migraineurs participants.…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations